KEPUASAN KARYAWAN TERHADAP PELAYANAN PENGEMUDI (DRIVER) MOBIL OPERASIONAL DI PT SARANA MULTI INFRASTRUKTUR (PERSERO) - Wawan Hari Subagyo; Dedi Stiyadi (Economicus : Jurnal Ekonomi dan Manajemen, 2021)
The objectives of this study are knowing the condition of the service quality of the operational car driver for the employees of PT Sarana Multi Infrastruktur (Persero), this is to find out how employees are satisfied with the operational car driver service at PT Sarana Multi Infrastruktur (Persero) and to find out the gap analysis of employee satisfaction with operational car driver services at PT Sarana Multi Infrasrtuktur (Persero). The results of the analysis show that the variables that satisfy consumers are 1). Tangible variable in the second question, namely the physical condition of the vehicle being driven by the driver according to the request. 2). The variable reliability (reliability) in the first question is the skill of the driver (driver) in driving operational vehicles. 3) Variable assurance (assurance) in the second question, namely, the driver of the operational car provides a sense of security in service to employees. the company has provided the best service, therefore the company must maintain the above variables. The variable that has not satisfied consumers is the variable reliability (reability) in the second question, namely the question of Timeliness in picking up and delivering employees and variable assurance (assurance) on the first question Driver (driver) Provides safety assurance in serving employees.